Generación de propuesta de sistemas modulares y súper modulares en base a la iconografía de la cultura Puruhá aplicables a propuestas de diseño - Vallejo Moreno, Jhoanna Katherine (2018)
The graphic design as discipline allows us to communicate visually a message making use of codes, iconic, linguistic, and pragmatic. As visual communicators, the graphic designers have the mission of facilitating the relation between the issuer and the recipient, doing that the message can be believable and lasting. Over the time, the graphic design in the Ecuador has been upsetting of the national context, taking like reference for the creation of the distinct messages, styles and proposals from other places of the world, dropping the use of visual elements with Andean significances, from the pre-Columbian cultures. By such reason is important the rescue of these visual elements, since thanks to its logic and significance have prevailed along the time. On having been in a context bombarded by so many not original visual elements of our culture, we must take in consideration the investigation of the pre-Columbian cultures for the innovation of the current graph, allowing with this to admit that we are heirs of a big cultural legacy that must be spread. The present investigation stand up with the necessity to spread the cultural wealth of our original peoples, by means of the study semiotic of the iconography of the ceramic pieces of the culture Puruhá, which served as foundation for the development of modular and super modular systems across a counterfoil of modular generation, which taking as a base these elements, and by means of the application of laws and composites categories, there were generated dynamic designs that were applied in different supports.